Integrating Buddhadhamma in Academic Excellence Administration - Thitapan, Phanthira; Visittapañño, Phramaha Phisit; Hapa, Yingsan (Journal of Graduate MCU KhonKaen Campus, 2023)
Academic administration to excellence along the Buddhist line by developing curriculum. It is important to manage education, to manage teaching, to achieve a given purpose. Systematic organization of complex knowledge or information and learning events using educational media Teaching is a learning aid in which teachers and students are users to help teach. The effectiveness of choosing teaching media. There are students at the center of teaching.Let students have their own personality traits, the courage to express themselves physically and mentally. There is a leadership position in participating in activities to promote unity among students. Responsibility for self-study is measured and evaluated as a formal activity. It is important to note that the implementation of educational activities is as follows: the aim of the women's The principle of Buddhism in academic management to excellence is the principle of Itthibat 4 which leads to academic success to excellence by integrating with the curriculum of teaching, teaching, and measuring and evaluating. Integrate Buddhist principles into excellence. Curriculums can be integrated by considering the curriculum to be consistent with the core curriculum. Local anti-teaching wisdom can be integrated with more centralized learning to encourage students to analyze. And take action by themselves in the field of teaching materials by applying them to teaching materials. More modern from the festival and collaborate to produce more local teaching materials, and Measurement and evaluation metrics can be integrated by considering measurement criteria and assess the results more clearly in order to improve school administration.